Aphra Behn and Bishop Burnet. (12th June 2020) - Wright, Gillian
Abstract: Aphra Behn's Pindaric Poem to Dr Gilbert Burnet is among her last and most politically outspoken works; published in 1689, shortly after the Revolution, it apparently declines an invitation from Burnet to write propaganda for the new Williamite regime. A copy of this poem, now held by Cambridge University Library, includes detailed handwritten corrections to both spelling and punctuation. As the poem is well printed, there is no obvious reason why these corrections should have been undertaken by either the printer or publisher, or an early reader. It is possible that the annotator was Behn herself, in anticipation of a second edition that she did not live to see into print.